Indications of Microsurgery in Soft Tissue Sarcomas - Viñals, J. M.; Rodrigues, T. A. Gomes; Sildenikova, D. Perez; Payro, J. M. Serra; Porté, J. A. Palacin; Suñe, C. Higueras; Ojeda, A. Lopez; Vidal, J. Muñoz; Dewever, M.; Lopez, C. Carrasco; Segu, J. O. Bermejo; Chavarria, F. A. (Journal of Reconstructive Microsurgery, 2012)
Sarcomas are uncommon tumors and free-margin surgical resection remains the single most important treatment in the curative therapy of soft tissue sarcomas. Refinements in surgical techniques have led to increased function preservation and limb salvage.Patients and Methods The records of patients (n = 41) who underwent microsurgical soft tissue reconstruction subsequent to resection of soft tissue sarcoma during the period 1998 to 2010 were reviewed and compared with a general nonmicrosurgery group (n = 188) in relation to clinicopathological characteristics, surgical procedures, postoperative complications, time until start of adjuvant radiation, functional outcome (Toronto Extremity Salvage Score, TESS), local recurrence, free survival, and disease-specific survival.Results Forty-one patients (age range: 23 to 95 years) received a total of 42 free flaps. When compared with the general nonmicrosurgery group, these patients presented significant differences with regard to location, histological grade, and neoadjuvant treatments. Complications were encountered in 10 cases, including 3 patients with complete flap loss and 1 patient with partial flap loss; other complications were cervical fistulae, knee arthritis, nonconsolidation, and wound infection. Extremity salvage was achieved in 90% (19/21) of limb sarcomas, with these patients showing adequate postoperative ambulation (TESS 77 ± 16) and adequate use of the upper extremity (TESS 66 ± 26). Two patients underwent amputation after recurrence. Disease-specific survival rates at 5 and 10 years were 79.49% and 76.93%, respectively.Conclusion The microsurgical repair of sarcoma defects is a reliable option that, though not free of complications, is necessary in selected cases such as patients receiving neoadjuvant treatments and those with head and neck location and high-grade tumors. The procedure enables both adequate oncosurgical resection and function preservation. Our microsurgical sarcoma reconstruction data, based on an observation period of 12 years and presenting the results of 42 free tissue transfers in 41 patients, adds further evidence to the previously published smaller series.
Keywords: sarcoma surgery; free tissue repair; microsurgery sarcoma